Penghasilan dan penerimaan minuman sukan isotonik berkos rendah dalam kalangan pelajar universiti - Khor, Siau Ying; Nur Nadirah Mohd Sanusi,; Sareena Hanim Hamzah,; Hasnah Haron,; Nik Shanita Safii, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Sports drinks consist of water, carbohydrates, and electrolytes specially formulated for athletes or individuals in need. However, coaches from the National Coaching Academy division experience budget constraints to obtain commercial sports drinks on a large scale to meet the needs of all athletes. Therefore, an experimental study was conducted to produce a low-cost isotonic sports drink (Rose Lemonade) with white sugar and brown sugar and evaluate its acceptance among university students through sensory evaluation. This study involved 50 panels with 25 students from UKM (non athletes) and 25 students from UM (athletes). The overall acceptance of brown sugar Rose Lemonade has an average score of 3.52 ± 0.97 compared to white sugar Rose Lemonade, which is 3.50 ± 1.07. The data analysis showed a non significant difference in the Kruskal Wallis test (p>0.05) for the overall acceptance of both types of sports drinks. In conclusion, this study showed that both white sugar and brown sugar Rose Lemonade isotonic sports drink formulations were acceptable to the panels. The findings of this study provide the formulation of cheap, and easy-making sports drinks. A suggestion for future research is to test the effectiveness of energy supply and electrolytes replacement and shelf life of this sports drink and produce a variety of flavors to meet individual tastes.